Model Green Human Resource Management: Concept and Implementing - Febrian, Wenny Desty (Siber Journal of Advanced Multidisciplinary, 2025)
The purpose of this literature research is expected to help hypothesize for future authors in determining research related to green HRM. The research article Green Human Resource Management Model: Concept and Implementing is a scientific literature article in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. Data collection techniques are using literature studies or conducting literature reviews of relevant previous articles. The data used in this research is secondary data, which comes from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Reward affects Green HRM; 2) Green Training affects Green HRM; 3) Green Behavior affects Green HRM; 4) Leader Commitment affects Green HRM; and 5) Organizational Culture has an effect on Green HRM.